Japan vs. Europe comparison of clinical evaluation methods for new antimicrobial drugs: On the difference in chronic airway infection cases between Ireland and Japan - Aoki, Nobuki; Kobayashi, Hiroyuki; Nagashima, Masahito; Matsumori, Hiroshi; Niki, Yoshihito (Japanese Journal of Chemotherapy, 2000)
Bridging studies are being increasingly conducted in the clinical development of novel antibacterial drugs, and the fact that cases of chronic airway infection in Japan and acute exacerbation of chronic bronchitis in Western countries are assessed differently is a particular issue. Although this matter has been discussed frequently with Western investigators, this study was conducted it was thought to be important to make definite comparisons to consider future clinical evaluation methods for antibacterial drugs to be developed in Japan. We visited the O'Doherty Clinic in Wexford, Ireland. The clinic had participated in a Trovafloxacin phase III study and had experience with many cases of acute exacerbation of chronic bronchitis. We reviwed the diagnosis, severity, and inclusion criteria in individual cases through discussion with local physicians in charge and radiologists, and compared them with standards in Japan. In a detailed study of 18 cases, acute exacerbation of chronic bronchitis was found to be regarded as the clinical diagnosis, and the clinical course, the presence of purulent sputum, and the results of microscopic examination of gram-stained specimens were found to be most important. The CRP value, the peripheral white blood cell count, and the presence or absence of fever, which are the criteria required of Japanese standards, were not evaluated. As a result, the number of mild cases is slightly greater in Western countries than in Japan. Chest X-ray studies, on the other hand, showed that 5 cases had structural disorders, such as old pulmonary tuberculosis, pulmonary emphysema, or bronchiectasis, and thus it was obvious that chronic bronchitis was not the only subject of the assessments. However, cystic fibrosis lung was not included, and cases persistently secreting Pseudomonas aeruginosa were also excluded. Because of the emphasis given to sputum gram staining, the rate of identification of causative organisms was high. Although the number of comparatively studied cases was limited this time, Western cases of acute exacerbation of chronic bronchitis essentially resembled Japanese cases of chronic airway infection, and the largest defference was considered to be the tendency for Japanese cases to be slightly more severe.